The Objectification of the Pedagogical Relationship in Everyday School Life - Nilda Stecanela (Universidade Federal do Rio Grande do Sul, 2018)
The text aims at reflecting on something recurrent in teachers' and students' narratives on their teacher and school experiences: the cultures of complaint. The observation of everyday life in schools shows that a feeling of discomfort accompanies teachers and students in the relation they establish. Although it is not named, what is at issue is the pedagogical relationship. The complaint acts as a mediator that brings to the field of reflection a pedagogical relationship that no longer sustains itself. Evidence of a relationship that occurs in parallel routes, with almost no connections, strengthens the argument for the existence of an objectified pedagogical relationship, far apart from a truly dialogical relationship.